2009
DOI: 10.1021/es803366d
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrocatalytic Removal of Bromate Using Ti/TiO2 Coated as a Photocathode

Abstract: These studies represent the rare use of a TiO2 material as a photocathode and the first application of photoelectrocatalysis for BrO3- removal. Photoelectrocatalytic reduction of BrO3- to Br- can reach 70% at neutral pH under an applied potential of -0.20 V versus SCE (saturated calomel electrode) after 75 min on the irradiated nanoporous thin-film TiO2-coated working electrode, which presented a flat band potential of -0.0274 V versus SCE. Regardless of the potential applied in these experiments, no BrO3- rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Although the use of TiO 2 as a suitable anode material to promote oxidation reaction on the irradiated working electrode has drawn the attention of several researchers, interestingly, some authors [8,168,169] have indicated that irradiated TiO 2 electrodes can operate in a polarization region where electrons are transferred from the n-type semiconductor to the electrolyte (cathodic current). In most n-type semiconductors, a potential barrier forms at the nonbiased semiconductor solution interface, preventing the bulk electrons from reaching the surface and reacting with electrochemical species at the expected potential [29].…”
Section: Removal Of Inorganic Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of TiO 2 as a suitable anode material to promote oxidation reaction on the irradiated working electrode has drawn the attention of several researchers, interestingly, some authors [8,168,169] have indicated that irradiated TiO 2 electrodes can operate in a polarization region where electrons are transferred from the n-type semiconductor to the electrolyte (cathodic current). In most n-type semiconductors, a potential barrier forms at the nonbiased semiconductor solution interface, preventing the bulk electrons from reaching the surface and reacting with electrochemical species at the expected potential [29].…”
Section: Removal Of Inorganic Pollutantsmentioning
confidence: 99%
“…Nowadays, photoelectrocatalysis is a technique with consolidated principles that has gained prominence and has been successfully applied in organic compound oxidation [4][5][6], inorganic ion reduction [7,8], microorganism inactivation [9,10], CO 2 reduction [11,12], and production of electricity and hydrogen [13][14][15][16]. The subject has since been explored by several researchers and reviews of deserving notoriety [13,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These technologies include electrocatalysis [35,[136][137][138], sonocatalysis/Fenton process [139], biodegradation [140][141][142][143][144], and wetland technology [145]. The combination of NTO photocatalysis with any of these techniques can not only improve the total efficiency of the degradation but also has the advantage of treating large quantities of wastewater (in real systems), especially with electrocatalysis, biodegradation, and wetland technology.…”
Section: Coupling With Other Treatment Technologiesmentioning
confidence: 99%
“…Figure 6b represents the efficiency (as a function of time) of different reaction systems employed in the decolorization of X-3B dye, in which the systems using TiO 2 photocatalysis and BDD anodic oxidation showed the highest activities. The removal of bromate by reduction to bromide [137] and the degradation of chlortetracycline [138] in high efficiencies were also achieved by photoelectrocatalysis using Ti/TiO 2 as the photocathode and photoanode, respectively. Another example for the synergic effect of different AOPs is the combined ultrasound-, Fenton-, and TiO 2 -photoassisted mineralization of bisphenol A [139].…”
Section: Coupling With Other Treatment Technologiesmentioning
confidence: 99%
“…Generally, second pollution and high consumption of reagents are inevitable in the removal process (Butler et al, 2005). It was reported by Paschoal et al (2009) that photoelectrocatalysis using a negatively applied potential to an irradiated TiO 2 -coated photocathode could be used to selectively reduce BrO 3 À to Br À , which was a good process with a high level of BrO 3 À conversion.…”
Section: Introductionmentioning
confidence: 99%